A dual pH and redox-responsive Ag/AgO/carboxymethyl chitosan composite hydrogel for controlled dual drug delivery. Issue 13 (1st September 2020) - Xu, Yanqin; Liu, Jie; Guan, Shumin; Cao, Yuan; Chen, Changguo; Wang, Dan
Abstract: A pH and redox dual-responsive composite hydrogel was developed, which was formed from triblock copolymer PEG-SS-PCL-SS-PEG and Ag/AgO/carboxymethyl chitosan (CMCS) hydrogel inclusion complexes. Dithiodipropionic acid and poly(ethylene glycol) (PEG) were esterified to synthesize a hydrophilic segment PEG-SS-COOH polymer containing a disulfide bond, and ε-caprolactone is ring-opened in Ar atmosphere to obtain a hydrophobic segment HO-PCL-OH homopolymer. The PEG-SS-PCL-SS-PEG triblock polymers were prepared by reacting the two in a certain ratio, and spontaneously assembled into micelles in an aqueous solution. Ag/AgO/CMCS composite hydrogels with a pH and redox dual-responsive were prepared by dispersing aspirin-loaded micelles into an Ag/AgO/CMCS hydrogel network loaded with another hydrophilic drug ciprofloxacin hydrochloride (CIP). The results showed that the micelles had redox sensitivity due to the insertion of disulfide bonds, and had certain stability within 24 h without reducing substances. In vitro simulated drug release test of composite hydrogel showed that the hydrogel network swelled or degraded, the micelles were lysed, and the release of the drug was triggered when the composite hydrogels were exposed to the micro-environment with high pH or high DTT concentration. Therefore, this composite hydrogel could potentially be one of the candidate materials for the dual drug delivery system.